INFORMATICS ENGINEERING STUDENTS’ DIFFICULTY IN TRANSLATING ENGINEERING TEXT - Wahana, Desi (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
This research is descriptive qualitative research with an embedded-case study research design. The purpose is to find out students' difficulty in translating informatics engineering text. To collect the data, this research used the descriptive method by content data analysis, FGD (focus group discussion), and questionnaire. The data were compiled in the English language and students would be asked to translate (Indonesian language) and fill a questionnaire in a google form. After collecting the data, it was validated by 2 raters through FGD. The findings of the study showed that students' difficulties in translating informatics engineering text were lack of vocabulary (60%), lack of understanding the grammar (13.3%), lack of understanding of context (13.3%), and lack of understanding of informatics engineering technical term (13.3%).